Active Compounds on Squid (Loligo sp.) Ink Extract Powder as Immunostimulant Candidate to Against Shrimp Disease - Rangga Idris Affandi; Mohamad Fadjar; Arning Wilujeng Ekawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
The business of developing shrimp farming cannot be separated from the existence of disease. In shrimp farming health management, disease prevention strategies can using various methods, one of which is immunostimulant. One alternative immunostimulant source that can be used to improve the body defense system in shrimp is squid (Loligo sp.) ink extract powder who has antibacterial ability. This study aims to analyze the presence of active compound in squid ink extract powder can be used as an immunostimulant candidate to against shrimp disease. The method used in this research is descriptive explorative and experimental method. This research was conducted with several stages of squid ink extraction until it becomes powder. Identification of squid ink extract powder is using FTIR and LC-MS test. The results showed that the squid ink extract powder contained alkaloid and carboxylic acid from the FTIR test results. Based on LC-MS test results, it was found that squid ink extract powder contained betaine, cinnamic acid, and choline compounds with large amounts of content. Betaine, cinnamic acid, and choline has several biological activity as antibacterial, antioxidant, antiviral, antifungal, etc. so that it can be used as an immunostimulant against shrimp disease.